Res sanctae in Roman pre-Christian period - Malenica, Antun (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
After the introductory remarks on ius divinum and the origins of the terms res sacra and res religosa the author analyses in his article the origins of the technical term of the Classical Roman law res sanctae and whether res sanctae of the pre-Christian period should be set aside from the classical legal category res divini iuris which, according to the sources, consists of res sacrae, res religiosae and res sanctae. Roman jurists of the classical period wrote about the roots of the term res sancta, but they did not address the latter question, however, it is addressed by the contemporary doctrine. When the roots of the term res sancta are in question, the author firstly reverts to the text D. 1.8.8pr.-1 in which Marcian says that the term 'sacred' (lat. sancta) originates from the plant called yarrow (lat. sagmen) which was carried by the representatives of Roman people as a symbol of their inviolability, and afterwards to the text D. 1.8.9.3 in which Ulpian connects the term sancta to a kind of the penalty (lat. sanctio) which protects that what should be inviolable. The author, however, finds that a text of the grammarian Servius offers a better foundation for the reconstruction of the origins of the term res sancta. Namely, Servius, when commenting on the text of Aeneid written by Virgil in the late old era, says that the word sanctum in Aeneid has the same meaning as if when it is said that something is dedicated to gods by means of blood (ad Aen., 12,200: et dictum ‘sanctum’, quasi sanguine consecratum) and that in Aeneid the word sancire, precisely speaking, denotes that something is made sacred, in other words dedicated to gods, by spilling the blood of a sacrificed animal lengthwise (Ibid., ‘Sancire’autem proprie est sanctum aliquid, id est consecratum, facere fuso sanguine hostiae.) The author emphasises that the oldest ritual mentioned by Romans, in which such a way of spilling blood could have occured, was the ritual of establishing the holy borders of the city of Rome. According to this ritual the borders were marked by a plough drawn by holy oxen. Since the ritual necessarily had to involve the sacrification ceremony for gods, it is not hard to assume that the augurs sprinkled the drops of blood of the sacrificed animal while walking behind the plough that was marking the future borders of the city. This marking of borders of a city, temple or land plot with blood drops is the most specific meaning of the word sancire written about by Virgil and Servius and it is, according to the author's opinion, the root of the word sanctum by means of which the technical term of classical law res sancta was constructed. About the question of whether res sanctae in the law of pre-Christian period were res divini iuris the author primarily indicates that there is a vast array of understanding in the doctrine: that they were res divini iuris, that they do not belong to that category and that they are between divine and profane things. After source analysis the author concludes that: 1. There is no legal or literary text in which it is said that res sanctae are not res divini iuris. 2. Gaius (G .2.8.), by observation that res sanctae are in a certain way (quodammodo) of the divine law, does not negate their belonging to the category of things of divine law, but forms two subcategories within this category. Res sacrae and res religiosae belong to one, and res sanctae to the other. With this, Gaius indicates that, regarding from the angle of layman science, the division of things of divine law into three kinds, res sacrae, religiosae and sanctae, by which all things are aligned into the same plane, is not entirely founded. Gaius, no doubt, could not have said more. Ius divinum and ius humanum were equally important elements of the legal system of the classical period, so the pontifical jurisprudence was the one to mould the rules, terms and legal categories of pontifical law. The res divini iuris category was not constructed based on one but three criteria. Res sacrae were associated with heavenly deities, res religiosae with sepulchral gods , and res sanctae with the religious character of a sanction. 3. The argumentation that res sanctae are not divini iuris due to their lack of true character of sanctity and the relation to deity which is present with res sacrae and res religiosae is unacceptable from the methodological point of view. This may be an observation of contemporary doctrine on those matters, but it is not an argument based on which one is allowed to conclude that the Romans did not consider them to be things of divine law, because the sources do not speak of different quality of sanctity among the res divini iuris. Finally, the author concludes that the contemporary doctrine of Roman law as a separate branch of historical jurisprudence should determine, when sources make it possible, what the attitudes of Roman legal doctrine on classifications of things were like, but must never introduce its own criteria of classification. Because of this, a properly posed question when it comes to res sanctae must be: how did Romans regard the city walls, city gates and land borders during their millennium-long history. According to the author, evolution is visible in this respect. When the first city borders were established upon the foundation of Rome, Romans undoubtedly considered them divine. It could not have been different when the power of religion of that time is kept in mind, as well as the religious character of the border marking rituals. In the 2nd century B.C., which is about nine hundred years after the foundation of the city, during which a new cultural and even religious ambience was created and it was significantly different from the one at the time of the foundation of Rome, the same things were divine only in a certain way (quodammodo divini iuris) for Gaius the jurist. For jurists who comprised the Epitome of Gaius in the late fifth century, in the cultural ambience dominated by Christianity, those things were no longer divine, not even in ‘some way’, but they were profane and lined up among things in public property. This is also the final point in the evolution of the pagan term res sancta. Coined within the frames of the old ius divinum, this term could not earn its place in the new law of the Christian church. In this law, which founded the new juridical system of the institutionalised church (ecclesiastica iura), within the term ‘divine’ there was no longer room for mundane things as city walls, city gates and land borders. This is confirmed by the constitutions in the Theodosian and Justinian’s Code.